Multiculturalism, Diversity and Containment on MuchMusic (Canada) and MTV (US) - Pegley, Karen (Canadian University Music Review / Revue de musique des universités canadiennes, 2002)
Since MTV and MuchMusic were launched in 1981 and 1984 respectively, both stations have been commended for their racially diverse video repertoires. As Homi Bhabha has observed, however, "multicultural" practices that encourage diversity should also be examined for simultaneous modes of containment and control (Bhabha, "The Third Space," 208). This analysis of both stations' video programming and rotation schedules from late 1995 suggests that as they expanded their repertories they established unique, carefully controlled, nationally-inflected relationships between dominant and marginalized musical traditions. Using examples by Euro-American and African diasporic performers, I explore how multiculturalism appears to be "celebrated" on MuchMusic and MTV while Western and non-Western representations are negotiated such that ethnocentric norms, which pervade North American cultural media, are never contested.